A 1‐Year Clinical and Radiographic Study on Hydrophilic Dental Implants Placed with and without Bone Augmentation Procedures. (17th August 2015) - Zumstein, Thomas; Sennerby, Lars
Abstract: Purpose: The aim of the present 1‐year clinical and radiographic study was to evaluate a hydrophilic dental implant when used in everyday cases in one clinic. The purpose was also to compare augmented with nonaugmented sites. Materials and Methods: The study group consisted of 50 consecutive patients treated with 159 dental implants (Proactive, Neoss Ltd, Harrogate, UK) in both mandibles and maxillae. Ninety‐two implants were placed with adjunct bone augmentation procedures, whereas 40 implants were placed in augmented maxillary sinus sites. A two‐stage procedure was used for 84 implants and a one‐stage procedure for 47 implants. Twenty‐eight implants were immediately loaded. Implant stability was measured with resonance frequency analysis (RFA) at placement and at prosthesis delivery. The patients were scheduled for checkups after 6 and 12 months in function with clinical and radiographic examinations. Marginal bone level measurements were performed in baseline and follow‐up intraoral radiographs. Results: Two implant failures in two patients were experienced after 1 year of loading, giving a survival rate of 98.7%. One implant in nonaugmented sites and one implant in conjunction with an augmentation procedure (sinus lift), giving a survival rate of 98.5% and 98.9% for healed and augmented sites, respectively (NS). RFA measurements showed 70.2 ± 9.5 ISQ at placement and 76.5 ± 5.9 ISQ ( p ≤ 0.001) after a mean healing time of 5.6 ± 1.6 months. The marginal bone loss amounted to 0.7 ± 0.7 mm after 1 year of loading. Frequency distribution showed bone gain or less than 1 mm bone loss for the majority of implants (69.3%), whereas 25.7% showed 1.1 to 2 mm, 5.0% more than 2 mm and no implants more than 3 mm of bone loss. Conclusions: The use of Neoss Proactive implants for prosthetic rehabilitation of consecutive patients resulted in predictable clinical and radiographic outcomes after 1 year of loading with no differences between augmented and nonaugmented sites.